Personal Hygiene Related to Healthy Food and Number of Infectious Diseases on Toddler of Scavanger Family - Maharani, Nabilla Fierdausya; Sumanto, Reni Pawestuti Ambari (BELIA: Early Childhood Education Papers, 2020)
This study aims to describe the personal hygiene and describe the factors that influence personal hygiene related to healthy food and the incidence of infectious diseases in toddlers from scavenger families in the Pekalongan City Landfill. This study uses a qualitative approach to the type of descriptive study. Data are collected through interviews, observation, and data collection techniques (documents). The main informant in this study is 3 parents who have toddlers, and triangulation informants 1 TPA chairman, 1 health center health worker, 1 Posyandu cadre. Data analysis technique uses the theory of Milles and Huberman. The validity of the data uses the method triangulation. The results of this study are that the family of TPA scavengers already know personal hygiene and every day serves healthy food that contains nutrition for their families, especially to children, by paying attention to personal hygiene when serving food, but there are still residents in the environment around the landfill who do not keep themselves clean properly and the living environment that does not receive enough attention from the cleanliness aspect. This results in infectious diseases such as diarrhea and ARI. Several factors that can influence personal hygiene include knowledge, attitudes, expectation practices, individual habits, and the physical environment in which they live. For parents who have toddlers to pay more attention to personal hygiene and healthy food, especially the physical environment in which they live to prevent infectious diseases.